PRE-SERVICE TEACHERS' RESISTANCE PRACTICES TO REFLECTION - MAZOR COHEN IRIT (Studia Universitatis Babes-Bolyai, 2019)
ABSTRACT. Educational preparation programs emphasize the importance of reflection in order to learn and promote preservice students' teaching. In the current research, five first year pre-service students who participated in a collective reflective discourse, in a small group in one of the educational colleges in Israel, expressed solid resistance to reflection. The aim of the research was to expose these resistance practices. The research question is: What resistance practices to reflection are used by primary school pre-service teachers (PST) at the beginning of the first preparation year? The research findings showed that the pre-service teachers (PST) used the following resistance practices in order to express their resistance to reflection: discursive practices of negative sentences, using examples from their previous experience to reflection as useless and accusing the pedagogical instructor; behavioral practices of their discourse manner and types of laughter. This article will start with a literature review on: reflection in teachers' education, and pre-service teachers' resistance practices. Next, there will be a description of the collective reflective discourse in a small group, followed by qualitative content analysis and findings. Finally, conclusions will be added and discussed.